Voltage Rise Regulation with a Grid Connected Solar Photovoltaic System - Akinyemi Ayodeji Stephen (MDPI AG, 2021)
Renewable Distributed Generation (RDG), when connected to a Distribution Network (DN), suffers from power quality issues because of the distorted currents drawn from the loads connected to the network over generation of active power injection at the Point of Common Coupling (PCC). This research paper presents the voltage rise regulation strategy at the PCC to enhance power quality and continuous operation of RDG, such as Photovoltaic Arrays (PVAs) connected to a DN. If the PCC voltage is not regulated, the penetration levels of the renewable energy integration to a DN will be limited or may be ultimately disconnected in the case of a voltage rise issue. The network is maintained in both unity power factor and voltage regulation mode, depending on the condition of the voltage fluctuation occurrences at the PCC. The research investigation shows that variation in the consumer’s loads (reduction) causes an increase in the power generated from the PVA, resulting in an increase in the grid current amplitude, reduction in the voltage of the feeder impedance and an increase in the phase voltage amplitude at the PCC. When the system is undergoing unity power factor mode, PCC voltage amplitude tends to rises with the loads. Its phase voltage amplitude rises above an acceptable range with no-loads which are not in agreement, as specified in the IEEE-1547 and Southern Africa grid code prerequisite. Incremental Conduction with Integral Regulator bases (IC + PI) are employed to access and regulate PVA generation, while the unwanted grid current distortions are attenuated from the network using an in-loop second order integral filtering circuit algorithm. Hence, the voltage rise at the PCC is mitigated through the generation of positive reactive power to the grid from the Distribution Static Compensator (DSTATCOM), thereby regulating the phase voltage. The simulation study is carried out in a MATLAB/Simulink environment for PVA performance.